Investigation of Efficiency and Thermal Performance of The Y-source Converters for a Wide Voltage Range - Brwene Salah Gadalla; Erik Schaltz; Yam Siwakoti; Frede Blaabjerg (Renewable Energy and Sustainable Development, 2015)
The Y-source topology has a unique advantage of having high voltages gain with small shoot through duty cycles. Furthermore, having the advantage of high modulation index which increase the power density and improve the performance of the converter. In this paper, a collective thermal and efficiency investigation has been performed in order to improve the reliability of the converter. Evaluation of relevant losses as ( switching, conduction, capacitor ESR, core and winding losses ), and evaluation of the junction temperature of the devices under 25C ambient temperature. The analysis is done for different voltage gain factors (2, 3, and 4), and different winding factor (4, and 5) using PLECS toolbox. The results shows that the higher the voltage gain and winding factor, the higher power losses and rising in the junction temperature of the device.